(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Unmanned aerial vehicles or drones are nowadays widely used in a broad field of scientific and commercial applications. Despite this, it is quite a new method for glacier mapping in polar regions and has a lot of advantages, as well as disadvantages over more classical remote sensing instruments. Here we examine the main issues associated with the application of drones for glacier research from our experience in Iceland, Greenland and the Antarctic. We use DJI Phantom series drones for the obtaining of aerial photographs and produce digital surface models (resolution of 8 – 16 cm) and orthomosaics (resolution of 2 – 4 cm) for glacier mapping. Several issues related to the ground control points, geolocation using Global Navigation Satellite System receiers and creation of final products are addressed as well. We recommend the further use of drones in remote polar areas because it allows obtaining very high-resolution orthomosaics and digital surface models that are not achieved by other methods. Short summer season, raw weather with precipitation and winds, limited drone flight duration and problems with connection cables are the main issues everyone can encounter working in polar regions but all issues can be restricted with careful planning and readiness to gather data whenever it is possible during all field campaign.